Vaccines, adjuvants and dendritic cell activators – Current Status and Future Challenges - Obeid, Joseph M. (Semin Oncol, 2015)
Cancer vaccines offer a low-toxicity approach to induce anticancer immune responses. They have shown promise for clinical benefit with one cancer vaccine approved in the U.S. for advanced prostate cancer. As other immune therapies are now clearly effective for treatment of advanced cancers of many histologies, there is renewed enthusiasm for optimizing cancer vaccines for use to prevent recurrence in early stage cancers and/or to combine with other immune therapies for therapy of advanced cancers. Future advancements in vaccine therapy will involve the identification and selection of effective antigen formulations, optimization of adjuvants, dendritic cell activation, and combination therapies. In this summary we present the current practice, the broad collection of challenges, and the promising future directions of vaccine therapy for cancer.